(3QSGdI aj JWgjQ GdMUQ hGdHhGQjs - (3GdYGedj, YR GdOjf, GdMSjf Hf YHO GdUeO Hf eMeO GdLHYj, J (B984(3g` (B1576(3es ((3GdeTgO GdZQhejs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg ceG jfHZj dLdGdg hLeGdg (B... (3Ef GdMUQ hGdHhGQj EPG CUGHgG Hhd Ch fLGSI QWHI hLnqaJ HGdTeS gd JWgQ Ce dG, hPgH CcKQ GdeJCNQjf Edi WgGQJgGs
(3BNQgG (B:s
(3BNQgG(B: (3hGdfU GdUQjM GdUMjM hGdGMJjGW HeKd gPg GdQhGjGJ GdVYjaI GdJj dG JajO YdeG hdG YedG hdgPG (B.. (3Cj eLJgO Sde ef efJbO hGj eLJgO Sde aj fbU habfG hEjGce ddYed HeG jMHg hjQVGg Cfg LhGO cQjes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 240s
(3GdPQjYI, L (B4: 147s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis